Analysis of the use of antibiotics in antibiograms of urine carried out by a clinical laboratory of the central-western region of Colombia - Rodríguez-Salazar, Carlos; Recalde-Reyes, Delia; Padilla-Sanabria, Leonardo (Universidad y Salud, 2017)
Introduction: Antibiotics are bactericidal/bacteriostatic molecules that control bacterial infections, its misuse favors multidrug or therapeutic failure in the case of naturally resistant bacterial strains, thus generating a health risk. Objective: To analyze the use of antibiotics in urine antibiograms carried out by a clinical laboratory (central-western region, Colombia). Materials and methods: A descriptive-retrospective study was made. Urine and antibiograms data were collected from April 2014 to June 2015 by a clinical laboratory in the central-western region of Colombia. The obtained data was confronted with the protocols described by the National Institute of Health of Colombia. Results: 1815 reports of urine and antibiograms were analyzed, identifying 18 bacterial species. In the 22.3% (403) of cases, antibiotics were evaluated and reported on naturally resistant microorganisms. Pseudomonas aeruginosa showed greater resistance and the antibiotic with the highest resistance was nalidixic acid (66.7%). Conclusion: The study showed that there is a problem in managing, reporting and interpreting antibiograms against naturally resistant microorganisms, which could favor the development of multidrug in sensitive microorganisms of bacterial flora. A review of national and international bibliography showed similar reports; however, no author mentions intrinsic resistances, so the data of antibiotic resistance would be over evaluated.